Microencapsulation by Spray drying of Cosmos caudatus Kunth. Extracts Using Gum Arabic: Influencing Factors and Controlled Release - Zahara, Izaz Aqeiluz; Sutrisno, Sutrisno; Ulfa, Siti Mariyah; Safitri, Anna (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Advanced drug delivery systems are required due to the increasing advancement in science and technology, with a common example being microencapsulation. This system is affected by the manufacturing conditions and slow release of bioactive compounds inside microcapsule. In general, phytochemicals in the edible plant, Cosmos caudatus Kunth, specifically flavonoids, offer several health benefits but are susceptible to degradation which reduces biological activities. Therefore, this study aimed to encapsulate extract using spray drying method, which can be used as wall material in Gum Arabic. Microencapsulated product was also tested for biological activities. The effect of microcapsule production was investigated, including the concentration of wall material and the stirring speed. Furthermore, the optimal conditions of microcapsule were selected based on the highest encapsulation efficiency. The results showed that a concentration of 4% (w/v) Gum Arabic and a stirring speed of 800 rpm were the optimal conditions, leading to a percentage release of 71.87%. Microcapsule under these conditions produced an IC50 value of 55.09 ± 0.57 ug/mL as an inhibitor of alpha-amylase enzyme. The characterization by scanning electron microscope (SEM) showed spherical forms with a mean diameter of 152.00 um. The bioactive substance in microcapsule was released at pH 2.2 and pH 7.4 for 30 to 120 min, with a percentage release of 38.05% and 95.14%, respectively. In conclusion, this study confirmed that microencapsulation played a crucial role in the development of plant extract with retained biological functions.